2002
DOI: 10.1186/1471-244x-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to right unilateral ECT in depressed patients: impact of comorbidity and severity of illness [ISRCTN39974945]

Abstract: Background: Recent electroconvulsive therapy (ECT) efficacy studies of right unilateral (RUL) ECT may not apply to real life clinics with a wide range of patients with major depressive episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Heikman et al (29) found that a homogenous group of patients with depression as the only indication for ECT responded better to ECT than a group of patients with comorbidities. In line with that study, our results suggest that patients without comorbid anxiety or substance dependence tended to have higher response rates than patients with these comorbidities, although the differences were not statistically significant, possibly due to the small number of participants.…”
Section: Comorbiditymentioning
confidence: 99%
“…Heikman et al (29) found that a homogenous group of patients with depression as the only indication for ECT responded better to ECT than a group of patients with comorbidities. In line with that study, our results suggest that patients without comorbid anxiety or substance dependence tended to have higher response rates than patients with these comorbidities, although the differences were not statistically significant, possibly due to the small number of participants.…”
Section: Comorbiditymentioning
confidence: 99%
“…An acute recovery prefers older age, 35 whereas heterogeneity, with consequential comorbidity, of a patient group can drastically diminish the response. 36 Some authors have also reported a dependence on the subtype of depression, 37 but some disagree with this. 38 Our study had a rather small but diagnostically homogenous sample that included only patients with psychotic depression.…”
Section: Discussionmentioning
confidence: 96%
“…65,100,101 Six trials used explicit diagnostic criteria. Two used ICD-10 5 criteria for major depression, 110,112 one 111 used DSM-III, 262 one used DSM-IV, 103 one used the Feighner 264 criteria 102 and one 107 used the criteria specified by Klein. 265 Four trials specified the severity of depression for inclusion according to the HRSD, with two 103,105 specifying scores on the 17-item HRSD of less than 17, one 111 specifying a score of less than 20 and one specifying scores of less than 22 on the 21-item HRSD.…”
Section: Chaptermentioning
confidence: 99%